Red Light‐Triggered Intracellular Carbon Monoxide Release Enables Selective Eradication of MRSA Infection - Cheng, Jian; Gan, Guihai; Shen, Zhiqiang; Gao, Lei; Zhang, Guoying; Hu, Jinming (Angewandte Chemie International Edition, 2021)
Carbon monoxide (CO) is an important gaseous signaling molecule. The use of CO‐releasing molecules such as metal carbonyls enables the elucidation of the pleiotropic functions of CO. Although metal carbonyls show a broad‐spectrum antimicrobial activity, it remains unclear whether the bactericidal property originates from the transition metals or the released CO. Here, we develop nonmetallic CO‐releasing micelles via a photooxygenation mechanism of 3‐hydroxyflavone derivatives, enabling CO release under red light irradiation (e.g., 650 nm). Unlike metal carbonyls that non‐specifically internalize into both Gram‐positive and Gram‐negative bacteria, the nonmetallic micelles are selectively taken up by S. aureus instead of E. coli cells, exerting a selective bactericidal effect. Further, we demonstrate that the CO‐releasing micelles can cure methicillin‐resistant S. aureus (MRSA)‐infected wounds, simultaneously eradicating MRSA pathogens and accelerating wound healing. Metal‐free CO‐releasing micelles can be selectively taken up by Gram‐positive bacteria, exerting a narrow‐spectrum bactericidal activity toward only Gram‐positive bacteria under red light irradiation. The CO‐releasing micelles synergistically eradicate MRSA pathogens and accelerate MRSA‐infected wound healing.